Heavy metal contamination in plants: sources, monitoring, and data-driven insights - Yadav, Arvind Kumar; Hasan, Mohseena; Kour, Simranjeet; Chandra, Ratna; Singh, Vivek Kumar; Noor, I. M.; Yahya, M. Z.A.; Singh, Har Mohan; Tripathi, Ashutosh (John Wiley and Sons, 2025)
The present study explores the impact of heavy metals on plant physiology and development, emphasizing sources, tracking methods, and health effects. It provides a comprehensive understanding and proposes strategies to mitigate these negative impacts. Advanced data analytics are used to track metal movement and concentration in plant species and environmental conditions. Heavy metals like cadmium, lead, and mercury disrupt plant growth, photosynthesis, and nutrient uptake, thereby reducing plant vitality and productivity. Data tracking reveals specific accumulation hotspots and adaptive mechanisms plants use to mitigate toxic effects. Effective tracking and data analytics are essential for understanding the extent of metal pollution. The study highlights the need for integrated approaches, such as phytoremediation, soil amendments, and regulatory measures, to address heavy metal stress. Future research should focus on developing more efficient tracking technologies and exploring genetic engineering solutions.